A Semiotic Analysis of Sarcasm Memes in @sarcasm_only Instagram Account - Sayid Arshad Al Hindwan; Nur Rosita (English Language and Literature, 2022)
This study aims to analyze the signs contained in 10 sarcasm memes on the @sarcasm_only Instagram account. The signs found were analyzed using Charles Sanders Peirce's theory, namely triadic meaning. In sign there are 3 aspects, namely Representamen, Object, and Interpretant. This research used descriptive qualitative method. While the data from this research are sarcasm memes in the form of text and images. This study focused on memes containing sarcasm found on the Instagram account @sarcasm_only that can be attributed to everyone regardless of their gender. In the analysis, 26 signs were found. 12 signs were found in the form of images and 14 signs in the form of text. Further researchers are advised to conduct research on sarcasm memes in the form of videos. Because this study examines sarcasm memes in the form of images, some aspects such as Index are rarely found.